2023
DOI: 10.3390/bs13020158
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of Personal Relative Deprivation and Subjective Well-Being in Japan

Abstract: Personal relative deprivation (PRD) refers to emotions of resentment and dissatisfaction caused by feeling deprived of a deserved outcome compared to some reference. While evidence suggests that relative deprivation based on objective data such as income affects well-being, subjective PRD has been less explored, especially in the East. This study evaluated the relationship between PRD and subjective well-being based on various aspects in the context of Japan. An online questionnaire survey, including the Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…22 This feeling often manifests as anger, resentment, depression, and other negative emotions, which can be detrimental to their psychological and behavioral development. 23 Influenced by social stereotypes, Chinese vocational college students tend to experience heightened relative deprivation. 24,25 Consequently, they often grapple with intensified negative emotions, including anxiety, depression, and stress.…”
Section: The Mediating Effect Of Negative Emotions Between Perceived ...mentioning
confidence: 99%
“…22 This feeling often manifests as anger, resentment, depression, and other negative emotions, which can be detrimental to their psychological and behavioral development. 23 Influenced by social stereotypes, Chinese vocational college students tend to experience heightened relative deprivation. 24,25 Consequently, they often grapple with intensified negative emotions, including anxiety, depression, and stress.…”
Section: The Mediating Effect Of Negative Emotions Between Perceived ...mentioning
confidence: 99%
“…Different societies and cultures assign varying degrees of importance to different types of SWB and happiness, and the factors that contribute to SWB differ across cultures (Diener et al 2018). However, it is essential to note that certain universal factors that contribute to SWB, such as good health and social relationships, also exist (Diener et al 2018;Ohno et al 2023). Prior research has shown that SWB is negatively related to materialistic tendencies (Brown and Kasser 2005;Lee 2019;Ohno et al 2022) and feelings of personal relative deprivation (Ohno et al 2023).…”
Section: Swbmentioning
confidence: 99%
“…However, it is essential to note that certain universal factors that contribute to SWB, such as good health and social relationships, also exist (Diener et al 2018;Ohno et al 2023). Prior research has shown that SWB is negatively related to materialistic tendencies (Brown and Kasser 2005;Lee 2019;Ohno et al 2022) and feelings of personal relative deprivation (Ohno et al 2023). Specifically, the pursuit of happiness through materialistic consumerism tends to prioritize external goals and may run counter to SWB, giving rise to materialistic desires and anxiety about status and financial success (Dittmar et al 2014;Furukawa and Lee 2023;Kasser 2018).…”
Section: Swbmentioning
confidence: 99%
“…Indeed, relative deprivation has been found to predict a range of actions, from international migration ( Stark and Taylor, 1991 ) to preference for immediate gratification and gambling urges ( Callan et al, 2011 ). Cross-cultural evidence for relative deprivation as a phenomenon and predictor of poor subjective wellbeing and political violence has been found among participants in Japan ( Ohno et al, 2023 ), Brazil, Turkey, Belgium, France ( Adam-Troian et al, 2020 ), the Netherlands, and Singapore ( van den Bos et al, 2015 ). Furthermore, Grant (2008) demonstrated that skilled immigrants in the Canadian labor market who experienced relative deprivation reacted with strong protest intentions and engagement in protest actions.…”
Section: Introductionmentioning
confidence: 99%